2016
DOI: 10.18352/ijc.618
|View full text |Cite
|
Sign up to set email alerts
|

Do institutions matter in neighbourhood commons governance? A two-stage relationship between diverse property-rights structure and residential public open space (POS) quality: Kota Kinabalu and Penampang, Sabah, Malaysia

Abstract: Despite the existing literature regarding institutional influence on traditional commons, there is still a comparative dearth of research that theorises property-rights structure and its impact on contemporary commons. This is particularly true for public open space (POS) governance: its management and utilisation and hence its quality, of which underinvestment and overexploitation leads to increasingly negative externalities and outcomes. An interdisciplinary study is employed here to depict the relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Although there are many available instruments to measure POS worldwide [17][18][19][20][21][22], many of them lack characteristics related to the place to be evaluated. For example, the EAPRS [18] and the BRAT-DO [17] are questionnaires used mainly in HICs, whose main characteristics are based on measuring aspects not related or not relevant to the Mexican context, such as water-related amenities, drinking fountains, and good maintenance.…”
Section: Development Of the Mexposmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many available instruments to measure POS worldwide [17][18][19][20][21][22], many of them lack characteristics related to the place to be evaluated. For example, the EAPRS [18] and the BRAT-DO [17] are questionnaires used mainly in HICs, whose main characteristics are based on measuring aspects not related or not relevant to the Mexican context, such as water-related amenities, drinking fountains, and good maintenance.…”
Section: Development Of the Mexposmentioning
confidence: 99%
“…Lastly, a study in 163 children (aged 8-9) found an increase of 25 min of moderate to vigorous physical activity per day if there was a playground in the POS [16]. In agreement with these attributes, various tools have been developed to assess objectively the physical aspects of the POS globally [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The government should provide better quality and an adequate number of UGS with close proximity (e.g., within walking distance, 400-500m), whereas the public should use the provided amenities and facilities responsibly and courteously. Therefore, this study offers a few takeaways to policymakers (local governments) that when designing and improving the provision of urban green spaces, the above variables should be taken into account since they influence users' preferences, consumption pattern and maintenance intention towards UGS (Ling et al, 2016;Ling, 2019) as well as their satisfaction and enjoyment, which consequently affect their WTP for UGS services. Despite the findings above, the study has limitations.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, despite the significant ecosystem services provided by UGS, the protection of UGS has been undervalued by the government due to insufficient resources in terms of budgets and manpower, thus resulting in a lack of UGS maintenance and management. This consequence adversely affects the UGS provision in terms of quantity and quality aspects; overused spaces (e.g., vandalised and misuse space) with no effective management will eventually become underused and disused (Ling, 2019;Ling et al, 2016Ling et al, , 2019. To address the above issues, sufficient public monetary contribution via taxation is suggested as an alternative to ensuring the continuity and sustainability of UGS services.…”
Section: Introductionmentioning
confidence: 99%
“…Sørensen, Bryson, and Crosby (2021, 277) maintain that public value "is defined through an often messy integration and alignment of what citizens expect will make things better for themselves and their loved ones." Commoning initiatives from the communities could lead to better utilisation and sustainability of urban resources (Ling et al 2016). In this context, the resolution of the tensions between 'commons' and 'the public' becomes critical to public problem-solving and co-creation of public-value outcomes.…”
Section: Introductionmentioning
confidence: 99%